Worldwide Predoctoral Dental Implant Curriculum Survey - P. Atashrazm; N. Vallaie; R. Rahnema; H. Ansari; M. Pour Shahab (Tehran University of Medical Sciences, 2011)
Objective: Predoctoral dental implant education is included in dental school teaching curricula in most of the developed and some developing countries; however, it was not introduced into undergraduate curriculum of some countries and Iranian dental schools. Our purpose was to investigate the status of the predoctoral dental implant education of dental schools in the world. Materials and Methods: One hundred-thirty five dental schools were randomly selected representing 62 countries divided into two regions. The first region included North America and Europe, and the second region comprised of Asia, South America and Africa. A questionnaire including onset year, lecture hours, lectures available on the internet, required textbooks, department jurisdictions, the year of dental school the course was offered, clinical and laboratory courses, implant systems used surgically and in restorative phase, and type of restorations treated by predoctoral students was mailed electronically to the predoctoral implant dentistry directors. Results: Ninety-two (68%) schools responded; of which 79 (86%) incorporated implant dentistry in their predoctoral teaching curricula, 39 (49%) offered surgical and prosthodontics courses in which students mainly observe. Of these 39 dental schools,28 (71%) and 11 (29%) dental schools are from the first and second region, respectively. Conclusion: A large percentage of responding schools included implant education in the predoctoral dental curriculum. Onset year of course, topics included in lecture series, lecture hours, faculty to student ratio and practical course vary among schools. Fifty percent of responding dental schools including Iranian dental schools do not have curriculum guidelines for predoctoral implant dentistry.